Explaining the Current Status of General Medicine Curriculum from the Perspective of Cancer Education Based on SWOT Analysis - Dariush Muslimi; Tahereh Aghamirzaee Mahali; Jamileh Aqatabar Roudbari; Farzin Sadeghi; Mostafa Javanian; Mohammad Ranaee (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Introduction: Given the rapid advancements in the field of medicine, it is essential to review current status of curricula both quantitatively and qualitatively. The present study aims to determine the current status of general medical curriculum with a focus on cancer-related topics and education based on Strengths, weaknesses, opportunities and threats (SWOT)analysis. Methods: This qualitative phenomenological study was conducted during the academic year 2022-2023 at Babol University of Medical Sciences, Babol, Iran. The study population consisted of 12 experts specialized in higher education, medical education, basic sciences, preclinical education, general medicine internships, oncology, and medical education experts, whom were selected through purposive sampling. Data were collected through document reviews and expert panel discussions, and were analyzed using SWOT analysis. Results: The results indicated that the existence of a national curriculum was identified as a strength, while the absence of an independent syllabus for cancer education was recognized as a weakness. In terms of opportunities, the implementation of transformation and innovation programs in medical education and the possibility of localizing curricula by universities were positively evaluated. However, student dissatisfaction with the quality of clinical cancer education and the theoretical and practical knowledge deficiencies of graduates in this area were identified as threats. Conclusion: To enhance the effectiveness and foster innovation in policy-making, cancer education, and clinical care, and to prepare future professionals, academic specialists and medical education authorities must leverage evidence-based strategies and academic experiences to purposefully integrate interdisciplinary collaboration in teaching cancer-related educational content into the general medical curriculum.